2013
DOI: 10.1631/jzus.a1300198
|View full text |Cite
|
Sign up to set email alerts
|

Development of non-premixed porous inserted regenerative thermal oxidizer

Abstract: Abstract:In this study, a porous inserted regenerative thermal oxidizer (PRTO) system was developed for a 125 kW industrial copper-melting furnace, due to its advantages of low NO x emissions and high radiant efficiency. Zirconium dioxide (ZrO 2 ) ceramic foams were placed into the combustion zone of a regenerative thermal oxidizer (RTO). Different performance characteristics of the RTO and PRTO systems, including pressure drop, temperature distribution, emissions, and energy efficiency, were evaluated to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The results showed that the diffusion combustion in porous media exhibits high stability [1619]. Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the diffusion combustion in porous media exhibits high stability [1619]. Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the diffusion combustion in porous media exhibits high stability [16][17][18][19]. Zhang et al [16] developed a 125 kW reciprocating flow porous medium diffusion combustion furnace.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced chemical mechanisms are used for the present simulation and two-step methane-air reaction is used as in equations. (11) and (12).…”
Section: B Chemical Kinetics Of Methane Combustionmentioning
confidence: 99%
“…Zhang et al [11] utilized DFC for a porous inserted regenerative thermal oxidizer system in an industrial coppermelting furnace. Using a one-temperature model it was found that the system achieved a significant reduction in the NOx emission level and a fuel saving of approximately 30% compared to a typical regenerative thermal oxidizer.…”
Section: Introductionmentioning
confidence: 99%